Genetic characteristics involving the PD-1/PD-L1/L2 and CD73/A2aR axes and the immunosuppressive microenvironment in DLBCL - Tingting Zhang; Zhenzhen Zhang; Xiubao Ren; Jin He; Zhengzi Qian; Bin Meng; Lei Jiao; Hengqi Liu; Lanfang Li; Lihua Qiu; Shiyong Zhou; Wenchen Gong; et al. (Journal for ImmunoTherapy of Cancer)
Background Targeting the PD-1/PD-L1/L2 (programmed cell death protein 1/programmed cell death ligand 1/ligand 2) pathway combined with other immunosuppressive signalings, such as CD73/A2aR (A2a adenosine receptor) adenosine signaling, has emerged as a promising strategy for cancer treatment. The genetic characteristics of these immune checkpoints need to be further investigated in diffuse large B-cell lymphoma (DLBCL).Methods We performed whole-exome sequencing/targeted deep sequencing to investigate the genetic characteristics of PD-1/PD-L1/L2 and CD73/A2aR. The immunosuppressive effect of these two pathways on the tumor microenvironment was evaluated via RNA sequencing. Single-cell RNA sequencing was further applied to investigate the dysfunctional CD8+ T cells. In addition, multiplex immunofluorescence staining was used to quantitatively assess the expression of dysfunctional CD8+ T cells in DLBCL.Results SP140 was identified as a novel translocation partner for PD-L1, and a new inversion was detected between PD-L1 and PD-L2, both leading to the upregulation of PD-L1 expression. CD73 genetic mutations did not increase mRNA and protein expression. Patients with genetically altered CD73 tended to have a better overall survival than patients with wild-type CD73. Both PD-1/PD-L1 and CD73/A2aR signaling mediated the immunosuppressive microenvironment in DLBCL. The numbers of CD8+ T cells with PD-1 and A2aR expression were positively correlated with the number of dysfunctional CD8+ T cells (R2=0.974, p=0.013). According to the grades of dysfunctional CD8+ T cells we defined, grade 1 dysfunctional CD8+ T cells, with either PD-1+ or A2aR+, were significantly associated with poorer survival than grade 0 dysfunctional CD8+ T cells, with both PD-1− and A2aR−; and patients with grade 2 dysfunctional CD8+ T cells showed the worst clinical outcomes.Conclusions This study describes the additional genetic basis of PD-L1 overexpression and characterizes certain genetic alterations of CD73/A2aR in DLBCL. The degree of T-cell dysfunction is correlated with clinical outcomes. Strategies that reverse T-cell dysfunction by inhibiting PD-1/PD-L1/L2, particularly in combination with CD73/A2aR, may show potential as effective therapeutic options for DLBCL.